Traveling, "Drive my Soul". Shared Narratives and Restitutions of Meaning - Luana Di Profio (University of Bologna, 2022)
In the fifth space-time dimension of the journey, in that invisible dimension of meaning, one also simultaneously enters the dimension of narration, in a double track that makes the dialogic dimension, traveling, a distinctive trait of traveling, both inside and outside oneself. The journey then becomes the occasion for a reinterpretation of meaning, the place of its return, the space within which to get lost and find oneself in a different articulation of oneself and one's identity, the forge, the alchemical atanor, where to live profound upheaval of oneself within a narrative and dialogic consciousness that makes the travel companion, the traveler, the other the focus and direction of our haughty representations and of our most unfathomable inner worlds. Because no one can tell only himself. We will therefore try to make people understand the special connection that exists between travel and narration, present within a literary tradition that crosses times and places, crossing the Middle Ages with Geoffrey Chaucer's Canterbury Tales up to the most recent Drive my Car by Murakami, in a common narrative and existential structure that unfolds precisely in the particularity of traveling together. Everything that happens to us while traveling becomes a form of narration that combines the lived experience of consciousness, the Erlebnis, the poetry of the word in expression, an expression of a deeper self that can manifest itself in its epiphany through the story of what we are while we travel, while we wander, while we walk in other places, with others, lost in walking on foot, by car or train, without space-time limits, in that way of flying over the world typical of flânerie.